2016
DOI: 10.1534/genetics.116.192898
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropeptides FLP-2 and PDF-1 Act in Concert To Arouse Caenorhabditis elegans Locomotion

Abstract: During larval molts, Caenorhabditis elegans exhibits a sleep-like state (termed lethargus) that is characterized by the absence of feeding and profound locomotion quiescence. The rhythmic pattern of locomotion quiescence and arousal linked to the molting cycle is mediated by reciprocal changes in sensory responsiveness, whereby arousal is associated with increased responsiveness. Sensory neurons arouse locomotion via release of a neuropeptide (PDF-1) and glutamate. Here we identify a second arousing neuropepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 47 publications
1
59
0
Order By: Relevance
“…We have shown that arousal following touch stimulation may involve a sequence of extrasynaptic neuromodulatory signals beginning with a FLP-20/FRPR-3-mediated signal conveying mechanosensory activity to RID. A signal involving multiple arousal neuropeptides released from RID has previously been shown to promote enhanced locomotor activity ( Chen et al., 2016 , Lim et al., 2016 ), consistent with data from our study showing that RID peptides are required for both locomotor and sensory arousal ( Figures 7 E and 7F). This wireless pathway complements the reflexive escape response involving wired synapses and gap junctions between mechanosensory neurons, premotor interneurons and motorneurons leading to reversals ( Chalfie et al., 1985 ) ( Figure 7 G).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We have shown that arousal following touch stimulation may involve a sequence of extrasynaptic neuromodulatory signals beginning with a FLP-20/FRPR-3-mediated signal conveying mechanosensory activity to RID. A signal involving multiple arousal neuropeptides released from RID has previously been shown to promote enhanced locomotor activity ( Chen et al., 2016 , Lim et al., 2016 ), consistent with data from our study showing that RID peptides are required for both locomotor and sensory arousal ( Figures 7 E and 7F). This wireless pathway complements the reflexive escape response involving wired synapses and gap junctions between mechanosensory neurons, premotor interneurons and motorneurons leading to reversals ( Chalfie et al., 1985 ) ( Figure 7 G).…”
Section: Discussionsupporting
confidence: 91%
“…While most C. elegans neurons contain modest numbers of dense core vesicles, generally peripheral to chemical synapses, RID signals predominantly through large varicosities that contain almost exclusively dense core vesicles ( Lim et al., 2016 ). Both transgenic reporter and expression profiling studies reveal expression of multiple neuropeptide precursor genes in RID ( Janssen et al., 2009 , Kim and Li, 2004 , Lim et al., 2016 ), including several previously linked to locomotor arousal ( Chen et al., 2016 ). RID makes a few chemical and electrical synapses with motorneurons and body muscle, but much of its effect on locomotion appears to be through neuroendocrine actions on the somatic neuromusculature ( Lim et al., 2016 , White et al., 1986 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Drosophila , loss of function of the RFamide neuropeptide sNPF reduces sleep, whereas stimulation of sNPF-expressing neurons promotes sleep ( Shang et al, 2013 ). Similarly, in C. elegans , overexpression of several members of the FLP family of RFamide neuropeptides promotes sleep ( Nath et al, 2016 ; Nelson et al, 2014 ; Trojanowski et al, 2015 ), while loss of function analysis revealed a requirement for select FLP neuropeptides in regulating sleep duration ( Chen et al, 2016b ; Iannacone et al, 2017 ; Nath et al, 2016 ; Nelson et al, 2014 ; Turek et al, 2016 ) or homeostasis ( Nagy et al, 2014 ). Based on these data, we reasoned that testing candidate vertebrate orthologs of invertebrate sleep regulators may be a fruitful strategy to identify neuropeptides that regulate vertebrate sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Although the CRF system appears to have been lost in nematodes [ 5 , 30 , 57 ], SEB-3 belongs to the same secretin superfamily of receptors as mammalian CRF receptors, as well as invertebrate PDF receptors. PDF peptides were previously shown to also regulate arousal responses in C. elegans [ 50 , 58 ]. NLP-49/SEB-3 may therefore be another member of the secretin family of GPCRs, which modulates behaviour in stress conditions.…”
Section: Discussionmentioning
confidence: 99%